2017
DOI: 10.1002/14651858.cd009881.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor modulators for endometriosis

Abstract: * The basis f or the assumed risk is the m ean control group risk across studies. The corresponding risk (and its 95% conf idence interval) is based on the assum ed risk in the com parison group and the relative effect of the intervention (and its 95% CI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 32 publications
0
25
0
2
Order By: Relevance
“…Other medications of interest are the levonorgestrel-releasing intrauterine system and mifepristone, which were not used in the studies included in this review. Nonetheless, their clinical utility may be explored as these have been shown to be effective in suppressing the menstrual cycles and relieving pain associated with endometriosis [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Other medications of interest are the levonorgestrel-releasing intrauterine system and mifepristone, which were not used in the studies included in this review. Nonetheless, their clinical utility may be explored as these have been shown to be effective in suppressing the menstrual cycles and relieving pain associated with endometriosis [98,99].…”
Section: Discussionmentioning
confidence: 99%
“…Mifepristone also reduces lesion size in animal models and patients (Kettel et al, 1996;Mei et al, 2010). In parallel with these findings, a systematic review of 10 randomized controlled trials assessing the efficacy of SRPMs for relief of endometriosis-associated pain concluded that mifepristone relieves dysmenorrhea and dyspareunia, with insufficient evidence of efficacy and safety of other SPRMs (Fu et al, 2017). SPRMs may be a promising new type of medication for clinical use, but their long-term efficacy remains to be proven (Whitaker et al, 2014).…”
Section: Novel Therapeutic Approaches Targeting Steroid Receptorsmentioning
confidence: 99%
“…Amenorrhoea is a common association and is classed as a 'side effect', although, lack of menstruation may be clearly beneficial in women with endometriosis-associated HMB. Doses <2.5 mg/day are less likely to be effective; however, based on the available evidence, clear conclusions on dosage cannot be made (Fu et al 2017).…”
Section: Mifepristone and Endometriosismentioning
confidence: 99%